Desumanização e violação dos direitos humanos nos cárceres de São Paulo: limites e possibilidades de enfrentamento - Nicoletti, Aparecida Eliane (2014)
This thesis tried to reflect on the processes of dehumanization and violation of the human rights of men and women in prision and identify the possibilities of expression about the generic-human inside the institution. In approach of this theme it talked about the creative work as the founding of the sociability, consciousness and the universality as well as the freedom being a concrete men s choice. Other issues were addressed to the routine not only in the extent of privileged place for the reproduction of alienation but also from its overcoming through art and political ethical praxis. It looked for placing the transformations of the work in capitalism from the 20th century, the working class criminalization and presenting a brief historic about the imprisonment in the state of São Paulo, after the 70th in perspective of contextualizing. The research focused on the analysis of letters sent by the imprisoned men and women to Prison Ministry which from them it was understood the profile and the conditions of the imprisonment, as well as the thematic workshops held at the Santa Ana Feminine Penitentiary to improve the knowledge about the violations of the women s rights and their ways of coping it. In summary, the analysis of the different ways of violation from the specialized bibliography, institutional documents, reading and review of letters and workshops had the main purpose to add to the reflection of incarceration in a daily full of infringements, in which the systems of dehumanization are intensified, being dominant but not absolute